Before Utopia : the making of Thomas More's mind - Dealy, Ross (University of Toronto Press, 2020)
"This unique study considers the influences of Stoic critics on the evolution of Thomas More's thought. The author argues that More's engaement with Erasmus's work radicalized his understanding of Christianity and shaped the writing of Utopia."--